Effect Of Water Stress On Stomatal Characters Of Twenty One Near Isogenic Lines Of Wheat (Triticum Aestivum L.) - Alam, AMS; Kabir, G; UD-Deen, MM; Hoque, E (Bangladesh Journal of Agricultural Research, 2011)
The present study was carried out to determine the effect of water stress on stomatal characters of flag leaf of wheat (Triticum aestivum L.) where five different irrigation regimes were considered as environments. Stomatal opening frequencies were significantly decreased by water stress in both the surfaces of the flag leaf in both irrigated and rainfed conditions in all the near isogenic lines of wheat. In rainfed condition, it was lower than irrigated condition. Similarly stomatal index also significantly differed in different irrigation treatments at three different positions in both adaxial and abaxial surface but under rainfed condition, it was lower than the irrigated condition in all the genotypes. The pore lengths of flag leaf in both adaxial and abaxial surfaces were found similar in size. It also varied among the different irrigations, but the variations were not remarkable. In rainfed condition, the pore lengths of different genotypes showed lower values than irrigated condition. Effects of water stress on stomatal pore breadths in both the surfaces were significantly decreased in rainfed condition. But in different irrigation conditions, stomatal pore breadth were non-significant among the genotypes. The effect of water stress on different stomatal characters in both surface of leaf in different lines of wheat were decreased. Keywords: Water stress; stomatal characters; wheat . DOI: http://dx.doi.org/10.3329/bjar.v36i1.9241 BJAR 2011; 36(1): 173-181